2020
DOI: 10.7717/peerj.9252
|View full text |Cite
|
Sign up to set email alerts
|

Decreased inhibitory control after partial sleep deprivation in individuals reporting binge eating: preliminary findings

Abstract: Background Poor executive functions are associated with dysregulated eating and greater caloric intake in healthy samples. In parallel, findings suggested that sleep deprivation impairs executive functions. Methods We investigated whether partial sleep deprivation impairs executive functions in individuals reporting binge eating (BE, N = 14) and healthy controls (C, N = 13). Switch cost and backward inhibition were measured using the Task S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
(43 reference statements)
1
6
0
Order By: Relevance
“…For instance, a recent pilot study found that elevated daily estradiol, when progesterone was also elevated, was associated with BE episodes in perimenopausal women [14]. Sleep disturbances and negative affect, both of which are common experiences of women during the menopausal transition [15], also are well-established risk factors for BE [16,17]. Additionally, psychosocial stressors, such as caregiving demands and interpersonal strain, may increase further risk for dysregulated eating behaviors, especially for women [18].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a recent pilot study found that elevated daily estradiol, when progesterone was also elevated, was associated with BE episodes in perimenopausal women [14]. Sleep disturbances and negative affect, both of which are common experiences of women during the menopausal transition [15], also are well-established risk factors for BE [16,17]. Additionally, psychosocial stressors, such as caregiving demands and interpersonal strain, may increase further risk for dysregulated eating behaviors, especially for women [18].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to test the hypothesis that insomnia symptoms may moderate the relationship between PC and executive functions as assessed using a task-switching paradigm. This paradigm was chosen as a valid tool to study switch cost and backward inhibition in healthy and clinical populations, as documented by several papers from our group ( Ballesio et al, 2018a , b , 2020 ; Cerolini et al, 2020 ) and other groups (e.g., Sdoia and Ferlazzo, 2008 ; Couyoumdjian et al, 2010 ). However, in the present study, we found that while RTs were significantly slower in alternating (ABA) and switching (CBA) when compared to repetition (AAA) trials, reflecting the switch cost, the difference between RTs in ABA and CBA trials was not significant.…”
Section: Discussionmentioning
confidence: 99%
“… 24–28 However, some other studies found no significant changes in inhibition control after PSR. 29 , 30 …”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28] However, some other studies found no significant changes in inhibition control after PSR. 29,30 Several factors may contribute to the inconsistencies in the literature. For example, some sleep deprivation studies were conducted outside of the laboratory, 24,27,28 and many confounding variables (eg, room temperature, noise, interactions with family members) may not have been well controlled.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation